Colaboração e Interação em Contextos Não Convencionais: aplicações e instalações artísticas e de entretenimento - Gadelha, Bruno; Castro, Thaís; de Freitas, Rosiane; Cardoso, Edna; Fuks, Hugo (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2018)
This paper presents an investigation that has been developed at the Federal University of Amazonas through projects involving concepts of collaborative systems(CS) and humancomputer interaction (HCI) in artistic-cultural and entertainment events scenarios. In the artistic scene, there have been projects involving music and interaction through sounds. In the scenario of large entertainment events involving crowds, the projects consider issues such as engagement, interaction and collaboration. In these unconventional contexts the importance of the integration between the SC and IHC areas is observed in order to achieve relevant results to change the behavior of the audience aiming at an active, participatory and interactive attitude in the field of the arts and entertainment for the crowds.